Effect of IBA- Chemical Formulations and Cutting Types on the Rooting Behaviour of Erythrina suberosa Roxb. in Relation to Biochemical Changes - Bandana, L. C.; Shamet, G. S.; Mundhe, A. D. (Indian Forester, 2011)
The study was conducted to determine the effect of IBA- chemical formulations and cutting types on rooting behaviour of Erythrina suberosa during monsoon and spring seasons. Cuttings set in spring exhibited overall better performance in all the rooting characteristics. Application of 0.6% IBA + 1% captan + 2% sucrose- talc significantly maximized sprouting, callusing, rooting and root characteristics (root number, root length and root dry weight). Cuttings of lateral type showed significantly better performance as compared to the terminal and sub- terminal ones. Maximum rooting (43.33%) and mean root dry weight (15.17 mg) were achieved when lateral cuttings were treated with 0.6% IBA + 1% captan + 2% sucrose- talc and planted in spring. The study also revealed that cuttings with higher levels of total phenol, total carbohydrate and C/N ratio and low level of nitrogen performed better.